If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18(1.09x)=13(1.07x)
We move all terms to the left:
18(1.09x)-(13(1.07x))=0
We add all the numbers together, and all the variables
18(+1.09x)-(13(+1.07x))=0
We multiply parentheses
18x-(13(+1.07x))=0
We calculate terms in parentheses: -(13(+1.07x)), so:We add all the numbers together, and all the variables
13(+1.07x)
We multiply parentheses
13x
Back to the equation:
-(13x)
5x=0
x=0/5
x=0
| 4n-7=0 | | r2-3r-28=0 | | 16v–10v=18 | | 5x+5=10x-30 | | 2x-6=63+5x | | 15q=6q-90 | | 3.8x-(-1-9.7x)= | | (3x+2)+x=134 | | 3z=2z–7 | | 2(x+6)-2=45-5x | | 3x-8=5x-44 | | 12^2-18x=0 | | 3×(x+1)+x=15 | | 1/2x+4=3 | | 30-4.x=18 | | y/10.24=8 | | -15.1y–13.77+7y=-7.4y–1.8 | | 146.85=(x+8.60+3.90) | | (x+12)+7x-2=180 | | -17x-1+-10x+17=-32x+1 | | 0=3x^2-24x+22 | | 3969=49(p+15) | | Y=3x^2-24x+22 | | 5x+2+5x+33=14x+3 | | x+12+7x-2=180 | | 1020=6(x+16) | | -2-3x=22 | | F(x)=3x^2-24x+22 | | 7–2d=3 | | 0.5x+6=0.8x | | 39+2x+1=3x+13 | | -6(6x-2)=-6(5x+5) |